2016
DOI: 10.1371/journal.pone.0157623
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related 1H NMR Characterization of Cerebrospinal Fluid in Newborn and Young Healthy Piglets

Abstract: When it comes to neuroscience, pigs represent an important animal model due to their resemblance with humans’ brains for several patterns including anatomy and developmental stages. Cerebrospinal fluid (CSF) is a relatively easy-to-collect specimen that can provide important information about neurological health and function, proving its importance as both a diagnostic and biomedical monitoring tool. Consequently, it would be of high scientific interest and value to obtain more standard physiological informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…In several related studies, these methods have been found optimal for following the possible consequences of inflammation caused by exogenous agents [47,48,49]. Sixty-six molecules were quantified, mainly pertaining to amino acids, short chain fatty acids and organic acids.…”
Section: Resultsmentioning
confidence: 99%
“…In several related studies, these methods have been found optimal for following the possible consequences of inflammation caused by exogenous agents [47,48,49]. Sixty-six molecules were quantified, mainly pertaining to amino acids, short chain fatty acids and organic acids.…”
Section: Resultsmentioning
confidence: 99%
“…1 H‐NMR spectra were recorded at 298K with an AVANCE III spectrometer (Bruker, Milan, Italy) operating at a frequency of 600.13MHz. Following Ventrella et al, the signals from broad resonances originating from large molecules were suppressed by a CPMG filter composed by 400 echoes with a τ of 400 μs and a 180‐degree pulse of 24 μs, for a total filter of 330ms . The HOD residual signal was suppressed by means of presaturation.…”
Section: Methodsmentioning
confidence: 99%
“…Following Ventrella et al, the signals from broad resonances originating from large molecules were suppressed by a CPMG filter composed by 400 echoes with a s of 400 ls and a 180degree pulse of 24 ls, for a total filter of 330ms. 27 The HOD residual signal was suppressed by means of presaturation. This was done by using the cpmgpr1d sequence, part of the standard pulse sequence library.…”
Section: Stool Metabolomicsmentioning
confidence: 99%
“…In this work, a pilot study was performed in order to obtain enough evidence about the feasibility of using ultra high performance liquid chromatography coupled to high resolution mass spectrometry metabolomics for the identification of metabolites implied in the process of maturation. Since there was little previous information available about the subject , performing this study was considered highly convenient before carrying out a larger one. In the spirit of keeping the animal usage down to a minimum, plasma samples collected from previous studies that were designed for other purposes—mainly blank samples for PK/PD studies— were employed.…”
Section: Introductionmentioning
confidence: 99%
“…Since there was little previous information available about the subject [2][3][4], performing this study was considered highly convenient before carrying out a larger one. In the spirit of keeping the animal usage down to a minimum, plasma samples collected from previous studies that were designed for other purposes-mainly blank samples for PK/PD studies-were employed.…”
Section: Introductionmentioning
confidence: 99%